Detection of Hantaan virus RNA from anti‐Hantaan virus IgG seronegative rodents in an area of high endemicity in Republic of Korea. (15th April 2016) - No, Jin Sun; Kim, Won‐keun; Kim, Jeong‐Ah; Lee, Seung‐Ho; Lee, Sook‐Young; Kim, Ji Hye; Kho, Jeong Hoon; Lee, Daesang; Song, Dong Hyun; Gu, Se Hun; Jeong, Seong Tae; Kim, Heung‐Chul; et al.
ABSTRACT: Hantaan virus (HTNV), of the family Bunyaviridae, causes hemorrhagic fever with renal syndrome (HFRS) in humans. Although the majority of epidemiologic studies have found that rodents are seropositive for hantavirus‐specific immunoglobulin, the discovery of hantavirus RNA in seronegative hosts has led to an investigation of the presence of HTNV RNA in rodents captured in HFRS endemic areas. HTNV RNA was detected in seven (3.8%) of 186 anti‐HTNV IgG seronegative rodents in Republic of Korea (ROK) during 2013–2014. RT‐qPCR for HTNV RNA revealed dynamic virus–host interactions of HTNV in areas of high endemicity, providing important insights into the epidemiology of hantaviruses.